2021
DOI: 10.1080/14413523.2021.1930951
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding culture: towards a new approach to preventing child maltreatment in sport

Abstract: There is now undeniable evidence of child maltreatment in sport. This has provoked the gradual proliferation of safeguarding research aimed at protecting children from harm in sport. Such research recognises the need for a comprehensive and holistic approach that addresses individual, interpersonal and systemic contributors to child maltreatment in sport. This study sought to provide such an approach by applying the wellresearched concept of safety culture to safeguarding children in sport. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Overall, this research serves to illustrate that there are indeed cross-cultural variations and hence cultural factors merit consideration. This supports recent theoretical perspectives which have advocated for the importance of contextual influences when analysing coach-athlete [12,13]. Furthermore, strong associations were found between maintenance strategies and satisfaction in both the UK and Japan.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, this research serves to illustrate that there are indeed cross-cultural variations and hence cultural factors merit consideration. This supports recent theoretical perspectives which have advocated for the importance of contextual influences when analysing coach-athlete [12,13]. Furthermore, strong associations were found between maintenance strategies and satisfaction in both the UK and Japan.…”
Section: Discussionsupporting
confidence: 86%
“…One social factor that has received less attention is the country and culture within which the coach-athlete interact [12,13]. One study examined the coach-athlete relationship in seven countries.…”
Section: Doi: 1034256/ijpefs2142mentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,48,49 Given the relational dynamics and systemic features of sport and society that permit maltreatment, scholars have suggested that all stakeholders who are invested in and derive value from sport must share in the responsibility to effectively safeguard athletes. 7,50 Moreover, given their responsibility to facilitate safe and healthy performance environments, 47,49,50 sport medicine practitioners' role in safeguarding will be discussed with a clinical focus in the final sections of this paper.…”
Section: The Shift To Safeguardingmentioning
confidence: 99%
“…Lastly, SCCs confirm the presence of a potential ethical blurring [76] and appear mindful of the existence of inexperienced and/or uneducated peers. As a result, they ask for accountability, education [48], and the development of best practices based on a holistic approach [77].…”
Section: Coachesmentioning
confidence: 99%